The Impact of Yoga on Memory Development of Students (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The importance of memory in education cannot be overstated, as it is fundamental to learning and knowledge retention. In recent years, yoga has been increasingly recognized as a holistic approach that offers various physical, mental, and emotional benefits. This research paper explores the impact of yoga on memory development, focusing specifically on students. By integrating ancient yogic practices with modern scientific understanding, this study aims to demonstrate how yoga enhances memory, attention, and cognitive functions, ultimately benefiting students in their academic endeavors. The study reviews existing literature, presents research findings, and offers practical applications of yoga in educational settings.